Pore characteristics of clay minerals in the Qingshankou shale,Songliao Basin, China: unravelling the effects of illitization - Jiang, Xiaohua; Zhu, Rukai; Wu, Songtao; Zhang, Jingya; Yu, Zhichao; Guan, Modi; Ding, Lihua (Frontiers in Earth Science, 2025)
IntroductionClay minerals are critical components of lacustrine shale systems, where their associated pores govern reservoir properties. The diagenetic transformation of these minerals, particularly illitization, profoundly impacts reservoir quality, yet the mechanisms driving illitization and its influence on pore evolution remain poorly understood. This study investigates the illitization processes and pore characteristics in the Cretaceous Qingshankou Shale (QSK shale) to elucidate their implications for unconventional hydrocarbon storage.MethodsCore samples from the QSK shale in the Gulong Sag, Songliao Basin, were analyzed using a multi-method approach: field-emission scanning electron microscopy (FE-SEM) for pore morphology, QEMSCAN® for mineralogical mapping, X-ray diffraction (XRD) for clay mineral quantification, and nitrogen adsorption for pore-size distribution analysis.ResultsKey findings include: (i) Clay minerals in the QSK shale are dominated by illite and illite/smectite mixed layers (average >40% content), with intense illitization yielding >60% illite in clay fractions. (ii) Pores within clay minerals (micropores and mesopores <50 nm in illite/illite-smectite; macropores 50–100nm and elongated pores >800nm in chlorite) constitute primary storage spaces, interconnected by microcracks. (iii) Illitization occurs via two pathways: transformation of illite/smectite mixed layers and albite alteration, with the former dominating. Porosity initially increases with illite content (up to ∼30%) but declines progressively beyond this threshold.DiscussionThe threshold effect of illitization on porosity highlights a critical balance between pore generation (via mineral dissolution) and occlusion (from authigenic illite precipitation). These findings provide a mechanistic framework for predicting reservoir quality in lacustrine shale systems, emphasizing the dual role of illitization in enhancing or degrading storage capacity depending on diagenetic maturity.